Anatomy and physiology of the lymphatic system: edema formation process and lymphatic drainage technique - Marques, Tauge Marione Leal da Silva (2020)
The lymphatic system is one of the main systems of the human body, responsible for the drainage of excess interstitial fluids, acts in parallel with the cardiovascular system and consists of a network of lymphatic vessels and capillaries that carry the lymph, collecting ducts and ganglia. Imbalances in this system can lead to the formation of edema, fluid accumulation between cells. Manual lymphatic drainage is a technique designed to help the lymphatic system perform its functions. The technique developed by Vodder and Estrid has gained worldwide visibility and consists of stimulating lymph nodes and directing lymph in its natural sense, presenting good results in the treatment of edema. For the accomplishment of this work the literature review method was used, using the databases SciELO, Google Scholar and Annals of Internal Medicine. As inclusion criteria were evaluated articles of the Portuguese language that specifically portrayed the physiology of the lymphatic system and the pathophysiology of edema, so that, at the end of reading, of the 65 articles evaluated, only 19 fit. With this research, it can be seen that there are several techniques of lymphatic drainage, a method used to assist the lymphatic system in the drainage of excess interstitial fluid, and regardless of the method used, the technique should be performed by qualified person and with smooth and slow movements, always respecting the anatomy and physiology of the human body.